Implantação e implementação da lei 12711/2012 no Instituto Federal de São Paulo - Campus Salto/SP: vieses da gestão democrática - Bogoni, Lucas (2023)
This work focuses on the issue of affirmative actions, more precisely those aimed at access to Higher Education. The object of study is the analysis of the implantation and implementation of Law 12.771/2012 at the IFSP Campus Salto, seen from the perspective of democratic management, understanding it from the aspects of participation, transparency and decentralization. This is an exploratory case study research, carried out based on the phenomenological paradigm with a qualitative approach. The main data collection technique is documental. We started with a survey of the state of knowledge, moving on to a history of the region where the object is located. The time frame is from 2012 to 2016, due to the implementation period established by the aforementioned law. A discussion on affirmative actions based on public policy formulation instruments was highlighted and the social nature of Law 12,711/2012 was discussed. After defining the concepts of democratic management, selecting and analyzing the documents, a discussion of the democratic biases of the quota policy at Campus Salto was carried out. Finally, it was noticed that Law 12,711/12 was implemented without the participation of the community and there was no discussion on the issue of quotas guided by the institution and actions to monitor quotas were not even instituted. The implementation process was centralized and transparency compromised by the lack of affirmative action follow-up.